A case of gastric metastasis originating from right-sided colon cancer 4 years after colectomy - Amal Khsiba; Manel Moalla; Moufida Mahmoudi; Asma Ben Mohamed; Yaakoubi Manel; Salwa Nechi; Houda Belfekih; Selim Zribi; Mouna Medhioub; Lamine Hamzaoui; Mohamed Moussadek Azzouz (Future Science OA)
The stomach is rarely a metastatic site of other primary cancers. Gastric metastasis from colonic cancer is exceptional. We hereby report a case of a 54-year-old male patient who underwent a right hemicolectomy for right-sided colon cancer. The pathology exam revealed well differentiated adenocarcinoma, it was classified stage IIb. Regular controls performed including colonoscopy were normal. Four years after colectomy, the patient was admitted for hematemesis with epigastric pain with detoriation of general condition . Gastroscopy revealed a large ulceroproliferative mass in the antropyloric region. Histology showed that this tumor was an adenocarcinoma similar to the primary right colon cancer, which led to the diagnosis of metastatic gastric cancer originating from colon cancer.